(untitled) (Journal Of Educational and Psychological Researches, 2016)
Our country faced lots of crises specially Wars and still living under the traumatic events. This would result in psychological disorder specially the Acute Stress Disorder (ASD). That’s if not treated, it will turn to be over Post Traumatic Stress Disorder(PTSD). Also not mentioning the shortage of recourses speaks about war and crises. That treat with its inflections psychologically and sociologically theses cases if happened. The importance of this study arise through it is objective to introduce a program for EMDR which give benefit for treat in health, social, educational institutes. Aims: The objective of this Study is the identification of a Test the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) program in reducing severity symptoms of Post Traumatic Stress Disorder (PTSD) through the following hypothesis: There are no differences of statistical value before and after implementing the EMDR in reducing severity of PTSD symptoms. Tools and Methods: Al-Kubaisy PTSD Scale was used. It is based upon DSM-IV criteria of the American Psychiatric Association (APA). It is a 45 items, self-rating scale. It was standardized and its reliability and validity were verified in Iraq. It was used in many studies in Iraq were supported. Study Sample: The threptic program sample was choosing one person, male, 40 years old, as a case study. EMDR was applied in this program. The result: The result of the current program find The effectiveness of the program with (0,5) as statistical indicator through correctional indicators which independent in correcting the program effectiveness and these results were linked to previous studies. The researchers also has a number of recommendations and suggestions.